Manajemen Pencegahan Hipertensi dengan Pemanfaatan Pemeriksaan Tekanan Darah pada Lansia - Riska Arsita Harnawati; Juhrotun Nisa (Jurnal Surya Masyarakat, 2023)
Elderly is someone who experiences increasing age accompanied by a decrease in body functions, including decreased heart function, one of which is hypertension. The prevalence of hypertension in Indonesia in the age group of 55-64 years was 45.9%, aged 65-74 years was 57.6% and aged 75 years and over was 63.8%. The purpose of this PKM is to provide information about the health conditions of the elderly, especially for the prevention of hypertension. The activity was carried out at Posyandu Pos 6 Gumayun, Tegal Regency, by counseling and checking blood pressure. The result of this activity is knowing blood pressure as a preventive effort or prevention of hypertension in the elderly.